COVID-19 Mechanisms in the Human Body—What We Know So Far - Kumar, Ashutosh; Narayan, Ravi K.; Prasoon, Pranav; Kumari, Chiman; Kaur, Gurjot; Kumar, Santosh; Kulandhasamy, Maheswari; Sesham, Kishore; Pareek, Vikas; Faiq, Muneeb A.; Pandey, Sada N.; Singh, Himanshu N.; et al. (Frontiers in Immunology, 2021)
More than one and half years have elapsed since the commencement of the COVID-19 pandemic and the world is struggling to contain it. Being caused by a previously unknown virus, in the initial period, there had been an extreme paucity of knowledge about the disease mechanisms, which hampered preventive and therapeutic measures against COVID-19. In an endeavor to understand the pathogenic mechanisms, extensive experimental studies have been conducted across the globe involving cell-culture based experiments, human tissue organoids, and animal models, targeted to various aspects of the disease viz. viral properties, tissue-tropism and organ-specific pathogenesis, involvement of physiological systems, and the human immune response against the infection. The vastly accumulated scientific knowledge, on all aspects of COVID-19 has currently changed the scenario from great despair to hope. Even though spectacular progress has been made in all of these aspects, multiple knowledge gaps are remaining which need to be addressed in future studies. Moreover, multiple SARS-CoV-2 variants have emerged across the globe since the onset of first COVID-19 wave, with seemingly greater transmissibility/virulence and immune escape capabilities than the wild-type strain. In this review, we narrate the progress made since the commencement of the pandemic regarding the knowledge of COVID-19 mechanisms in the human body, including virus-host interactions, pulmonary and other systemic manifestations, immunological dysregulations, complications, host-specific vulnerability, and long-term health consequences in the survivors. Additionally, we provide a brief review of the current evidence explaining molecular mechanisms imparting greater transmissibility and virulence, and immune escape capabilities to the emerging SARS-CoV-2 variants.